Peran Tiktok Dalam Meningkatkan E-Commerce Global - Yolanda Br.Sihaloho; Vini Andayani Manik; Daniel Martinus; Lenti Susanna Saragih; Aurora Elise Putriku (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The popular short video platform TikTok, has emerged as a major player in the global e-commerce landscape. This research aims to understand the role of TikTok in increasing global e-commerce through a literature study. The main aim of this research is to understand how Tik Tok can improve global e-commerce. This research uses a qualitative approach with a literature study method. Data was collected from a variety of sources, including scientific journals, news articles, and industry reports. Data was analyzed using qualitative content analysis techniques. This research found that TikTok can increase global e-commerce through several mechanisms, including: Increasing brand awareness and consumer engagement. Driving impulse purchases and conversions Building community and customer loyalty and Facilitating influencer marketing and brand collaborations TikTok is a powerful tool that businesses can use to scale global e-commerce. Businesses looking to capitalize on TikTok must develop an effective strategy that leverages the power of the platform.